A key review on graph data science: The power of graphs in scientific studies - Das, Resul; Soylu, Mucahit (Elsevier, 2023)
This comprehensive review provides an in-depth analysis of graph theory, various graph types, and the role of graph visualization in scientific studies. Graphs serve as powerful tools for modeling and analyzing complex systems in diverse disciplines. The introduction highlights the importance of graphs as a visual representation in scientific research, enabling a better understanding of complex data. Infographics and knowledge graphs have gained significant popularity in recent years due to their effectiveness in conveying information. The review starts by exploring the foundations of graph theory, covering key concepts, algorithms, and applications. It discusses the different types of graphs, including directed, undirected, weighted, and bipartite graphs, and their specific use cases in scientific studies. Special attention is given to special graphs, such as complete graphs, trees, and social networks, which have unique properties and play a significant role in various scientific domains. The review showcases their applications and contributions in fields like biology, social sciences, network analysis, and data mining. Graph visualization emerges as a crucial aspect of understanding and interpreting complex data structures. The review emphasizes the challenges and advancements in graph visualization techniques, enabling researchers to effectively communicate and analyze graph-based information. In conclusion, this comprehensive review serves as a valuable resource for researchers in understanding the principles and applications of graph theory in scientific studies. The exploration of graph types, special graphs, and graph visualization techniques provides insights into the diverse uses and potential of graphs in various scientific disciplines.
Keywords: Graph theory; Graph types; Special graphs; Graphs in science; Graph visualization